2020
DOI: 10.3390/molecules25112649
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid and Controlled Release: A Review

Abstract: Hyaluronic acid (HA) also known as hyaluronan, is a natural polysaccharide—an anionic, non-sulfated glycosaminoglycan—commonly found in our bodies. It occurs in the highest concentrations in the eyes and joints. Today HA is used during certain eye surgeries and in the treatment of dry eye disease. It is a remarkable natural lubricant that can be injected into the knee for patients with knee osteoarthritis. HA has also excellent gelling properties due to its capability to bind water very quickly. As such, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(148 citation statements)
references
References 134 publications
3
120
0
2
Order By: Relevance
“…For early osteoarthritis, enhancing joint aqueous lubrication, supplemented with anti‐inflammatory drugs, can effectively alleviate the progression of osteoarthritis. [ 3,4 ] Ball bearing, one of the major rolling bearings, connecting two relatively moving machine parts in a manner that the friction resistance is minimal, has been widely used in manufacturing various industrial equipment. [ 5 ] A ball bearing is composed of two relative moving grooved tracks and slippery balls in the groove, of which the balls roll in the tracks, turning the sliding friction of the two tracks into negligible rolling friction, and thus reducing the wear of the tracks.…”
Section: Introductionmentioning
confidence: 99%
“…For early osteoarthritis, enhancing joint aqueous lubrication, supplemented with anti‐inflammatory drugs, can effectively alleviate the progression of osteoarthritis. [ 3,4 ] Ball bearing, one of the major rolling bearings, connecting two relatively moving machine parts in a manner that the friction resistance is minimal, has been widely used in manufacturing various industrial equipment. [ 5 ] A ball bearing is composed of two relative moving grooved tracks and slippery balls in the groove, of which the balls roll in the tracks, turning the sliding friction of the two tracks into negligible rolling friction, and thus reducing the wear of the tracks.…”
Section: Introductionmentioning
confidence: 99%
“…Particular interest is aroused by the biological properties of materials based on hyaluronic acid. Still, for the development and technology of advanced wound healing [ 26 ], drug delivery systems with controlled release [ 27 ], and polymer scaffolds [ 28 ], knowledge of the molecular weight dependency on the abovementioned properties is necessary. Our paper is one of the first to collect brief data on the structure, viscosity, density, surface tension, cohesive/adhesive, hydrodynamic and degradable properties of hyaluronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 9 , it can be demonstrated that the initial release rate of the drug from the HA-FS-NTF was retarded due to incomplete gel formation, but the release of fluconazole was gradual following complete hydration of the gel and remained at a steady state thereafter owing to pseudoplastic flow. Swelling of the polymer due to hydration led to a change in the physical and chemical parameters of the hydrogel configuration, to tune the porous structure uniformly [ 37 ]. The decreased release of fluconazole from the suspension and even from the gel might be due to a larger particle size or a less porous configuration, whereas the development of the nanotransfersome delivery facilitated the release of the drug from the semipermeable membrane owing to the smaller vesicle size and enhanced solubility.…”
Section: Resultsmentioning
confidence: 99%